2006
DOI: 10.1126/science.1120034
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Monitoring by Wireless Communication Networks

Abstract: The global spread of wireless networks brings a great opportunity for their use in environmental studies. Weather, atmospheric conditions, and constituents cause propagation impairments on radio links. As such, while providing communication facilities, existing wireless communication systems can be used as a widely distributed, high-resolution atmospheric observation network, operating in real time with minimum supervision and without additional cost. Here we demonstrate how measurements of the received signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
277
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 413 publications
(304 citation statements)
references
References 3 publications
0
277
1
1
Order By: Relevance
“…(4), calls for alternative sources of near-surface rainfall information. Microwave links from operational cellular telecommunication networks may be used for rainfall monitoring (5,6), potentially over large parts of the land surface of the earth. Along such links, radio signals propagate from a transmitting antenna at one base station to a receiving antenna at another base station (Fig.…”
mentioning
confidence: 99%
“…(4), calls for alternative sources of near-surface rainfall information. Microwave links from operational cellular telecommunication networks may be used for rainfall monitoring (5,6), potentially over large parts of the land surface of the earth. Along such links, radio signals propagate from a transmitting antenna at one base station to a receiving antenna at another base station (Fig.…”
mentioning
confidence: 99%
“…In 2006, researchers demonstrated that they could estimate how much precipitation was falling in an area by comparing changes in the signal strength between communication towers 1 . But mobile-phone companies were reluctant to give researchers access to their signal data, and the field progressed slowly.…”
Section: Rain Forecasts Go Mobilementioning
confidence: 99%
“…As weather conditions and atmospheric phenomena cause impairments on radio links, wireless communication networks provide built-in environmental monitoring tools, as was recently demonstrated for rainfall (Messer et al, 2006(Messer et al, , 2007 and areal evaporation observations. In this paper we introduce a new technique to measure atmospheric humidity using data collected by wireless systems.…”
Section: Introductionmentioning
confidence: 97%